Cellular plasticity facilitates phenotypic change in a dominant coral’s Symbiodiniaceae assemblage - Anthony, Colin J.; Lock, Colin; Taylor, Brett M.; Bentlage, Bastian (Frontiers in Ecology and Evolution, 2023)
Coral-associated dinoflagellates (Symbiodiniaceae) are photosynthetic endosymbionts that influence coral acclimation, as indicated by photo-endosymbiotic phenotypic variance across different environmental conditions. Symbiont shuffling (shifts in endosymbiont community composition), changes in endosymbiont cell density, and cellular plasticity have all been proposed as acclimation mechanisms. However, few studies have been able to partition which of the three strategies were responsible for observed phenotypic variance. Using a combination of metabarcoding and flow cytometry, we simultaneously characterized Acropora pulchra-associated Symbiodiniaceae assemblages at the community, population, and individual level under natural environmental conditions to deduce whether seasonal phenotypic change and site-related phenotypic variation of Symbiodiniaceae assemblages is a product of symbiont shuffling or cellular plasticity. Symbiodiniaceae assemblages displayed season-specific phenotypic variance, while Symbiodiniaceae community composition was geographically structured and cell density showed limited data structure. Based on these patterns, we reveal that cellular plasticity of Symbiodiniaceae was the source of a phenotypic variation, thus indicating that cellular plasticity is a mechanism for acclimation to mild environmental change.